Effect of different doses of N, P and K on the content of total soluble proteins in cape gooseberry leaves Physalis peruviana L. (Solanaceae) - Ramos Otiniano, Cynthia Catheryne; Programa de Estudio de Medicina Humana, Universidad Privada Antenor Orrego (2023)
Cape “gooseberry” Physalis peruviana L. is a Solanaceae of great economic importance due to the high nutritional value of its fruits. It is known that the use of a good NPK fertilization scheme allows to achieve increases in the content of nutrients such as proteins. The objective of this work was to determine the effect of different doses 160-50-160; 225-70-275; 300-100-450 of NPK respectively on the content of total soluble proteins in cape goosberry leaves. Total soluble protein content was determined with the Bradford method. Cape goosberry plants treated with NPK 300-100-450 showed higher PST content (31.04 ug/g sample), with significant differences (p<0.05) compared to the control. The NPK 225-70-275 treatment showed a value of 23.08 ug/g total soluble protein sample, while the lowest protein value was obtained with the NPK 160-50-160 treatment (9.81 ug/g sample). It is concluded that the different concentrations of N, P and K cause variation in the total soluble protein content of cape “gooseberry” Physalis peruviana L. (Solanaceae), with the plants treated with NPK 300-100-450 showing the highest protein content.